2014
DOI: 10.1245/s10434-014-3773-8
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in Histopathologic Evaluation of Melanoma Sentinel Lymph Node Biopsy with Clinical Follow-Up: Results from a Prospectively Collected Database

Abstract: There appears to be a small yet significant rate of discordance in diagnosis of the SLN for melanoma after expert histopathologic review. The implications of this discordance and revision of diagnosis is substantial. Expert histopathologic review of the SLN warrants consideration to provide the most accurate prognostic information and optimal patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…4 However, many patients with a good prognosis (early stage) still experience metastases, and clinicopathologic staging features are subject to variations in interobserver interpretation and reporting, [5][6][7] discordance that affects melanoma staging and ultimately patient management decisions. [8][9][10][11] With increasing cancer care costs, tools for improved risk prediction that more precisely guide resources toward high-risk patients are critical. 12 The 31-gene expression profile test has been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, many patients with a good prognosis (early stage) still experience metastases, and clinicopathologic staging features are subject to variations in interobserver interpretation and reporting, [5][6][7] discordance that affects melanoma staging and ultimately patient management decisions. [8][9][10][11] With increasing cancer care costs, tools for improved risk prediction that more precisely guide resources toward high-risk patients are critical. 12 The 31-gene expression profile test has been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…MSLT-I concluded that although 30 initial cases may yield a high rate of SLNB accuracy, 25 additional cases further increases SLNB proficiency . Misdiagnosis rates approaching 10% also occur in the absence of expertise in the histopathologic interpretation of SLNB for melanoma …”
Section: Resultsmentioning
confidence: 99%
“…• Inappropriate, incomplete removal of primary melanoma, with errors in Breslow thickness, ulceration and mitoses estimation; initial wide-excision of the primary tumour that may interfere with the subsequent SLNB procedure; inadequate detection, resection and evaluation of (sentinel) lymph nodes (Dandekar et al, 2014) • Different use of diagnostic terms/histopathological criteria by pathologists (Patrawala et al, 2016); incomplete histopathological reports; and not using the most recent TNM classification (Niebling et al, 2013) • Insufficient knowledge of and experience in detection and treatment of satellite or in-transit metastasis…”
Section: Stagingmentioning
confidence: 99%